Comparison of antibiotic accumulation in appendix with various methods of its injection (Bangladesh Journal of Medical Science, 2021)
Relevance of the problem: In respect that, lack dynamic of morbidity incidence of acute appendicitis and frequency of postoperative complications, against the backdrop of increasing the number of antibiotics. The problem of prevention of purulent-inflammatory complications during its surgical treatment remains relevant.Materials and methods: The authors compared the intensity of accumulation of ceftriaxone in the appendix tissues depending on the method of injection.Results: It turned out that with the intramuscular injection of ceftriaxone in 1–2 hours before the operation, its accumulation in appendix in an amount sufficient to delay the growth of the laboratory culture of Escherichia coli is not observed. After intravenous injection of the drug, accumulation occurs slowly, significantly far behind to the lymphotropic technique. With the lymphotropic injection of ceftriaxone, 1 hour before the operation, a dose of growth retardant culture test is already fixed, and with the intjection of 2 hours before the operation – the dose of ceftriaxone practically corresponds to the maximum possible, that is, the action of a “pure” antibacterial drug.Conclusions: The method of selecting antibiotic therapy for acute appendicitis is the introduction of ceftriaxone by lymphotropic route.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.268-273